β subunits of voltage-gated calcium channels in cardiovascular diseases - Loh, Kelvin Wei Zhern; Liu, Cong; Soong, Tuck Wah; Hu, Zhenyu (Frontiers in Cardiovascular Medicine, 2023)
Calcium signaling is required in bodily functions essential for survival, such as muscle contractions and neuronal communications. Of note, the voltage-gated calcium channels (VGCCs) expressed on muscle and neuronal cells, as well as some endocrine cells, are transmembrane protein complexes that allow for the selective entry of calcium ions into the cells. The α1 subunit constitutes the main pore-forming subunit that opens in response to membrane depolarization, and its biophysical functions are regulated by various auxiliary subunits – β, α2δ, and γ subunits. Within the cardiovascular system, the γ-subunit is not expressed and is therefore not discussed in this review. Because the α1 subunit is the poreforming subunit, it is a prominent druggable target and the focus of many studies investigating potential therapeutic interventions for cardiovascular diseases. While this may be true, it should be noted that the direct inhibition of the α1 subunit may result in limited long-term cardiovascular benefits coupled with undesirable side effects, and that its expression and biophysical properties may depend largely on its auxiliary subunits. Indeed, the α2δ subunit has been reported to be essential for the membrane trafficking and expression of the α1 subunit. Furthermore, the β subunit not only prevents proteasomal degradation of the α1 subunit, but also directly modulates the biophysical properties of the α1 subunit, such as its voltage-dependent activities and open probabilities. More importantly, various isoforms of the β subunit have been found to differentially modulate the α1 subunit, and post-translational modifications of the β subunits further add to this complexity. These data suggest the possibility of the β subunit as a therapeutic target in cardiovascular diseases. However, emerging studies have reported the presence of cardiomyocyte membrane α1 subunit trafficking and expression in a β subunit-independent manner, which would undermine the efficacy of β subunit-targeting drugs. Nevertheless, a better understanding of the auxiliary β subunit would provide a more holistic approach when targeting the calcium channel complexes in treating cardiovascular diseases. Therefore, this review focuses on the post-translational modifications of the β subunit, as well as its role as an auxiliary subunit in modulating the calcium channel complexes.